Penerapan Sistem Penilaian Kinerja Berbasis E-Kinerja Terhadap Prestasi Kerja Pegawai Melalui Kepuasan Kerja Sebagai Variabel Intervening Pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Banyuwangi - Dwi Rafita Mukti; Sri Wahyu Lelly Hana Setyanti; Lilik Farida (e-Journal Ekonomi Bisnis dan Akuntansi, 2019)
This study aims to knowing the influence of performance appraisal system based on e-performance on employee achievement through job satisfaction as an intervening variable on Dinas Kependudukan dan Pencatatan Sipil Kabupaten Banyuwangi. This study is causal research, it means problem characteristics research in a form cause-effect between two variables or more. Population is employees of Dinas Kependudukan dan Pencatatatn Sipil Kabupaten Banyuwangi with the amount 80 employees. The sampling method for this study was doing with purposive sampling technique and it has been gotten 37 respondents as samples. Data analysis method is Path Analysis. The hypothesis of research are performance appraisal based on e-performance has significantly affected job achievement, performance appraisal based on e-performance has significantly affected job satisfaction, and job satisfaction has significantly affected job achievement. The result of study was performance appraisal based on e-performance has positive and significantly affected employees achevement. It means performance appraisal based on e-performance can increase employee achievement. Performance appraisal based on e-performance has positive and significantly affected job satisfaction on employees. It means performance appraisal based on e-performance can increase job satisfaction on employees. Job satisfaction has positive and significantly affected employees achievement. It means the employees successfully in doing the tasks which have been given by company can increase job satisfaction which got. Keywords: Performance Appraisal, E-Performance, Job Saticfaction, employee acievement.